ANCIENT ASSYRIAN-BABYLONIAN GARDENS. - Kholmurotov Ramziddin Isomiddinovich.; Rakhmonova Mahfuza Kholmurodovna. (Western European Studies, 2024)
The countries of Mesopotamia - Assyria-Babylonia - occupied the territory of the basin of the Tigris and Euphrates rivers, flowing into the Persian Gulf. In this area the plains are covered with dense forests. There are many canals in the forested areas, and fish and bird species are widespread. Large groves of wild palm trees have grown here. Fruit trees include figs, peaches, pomegranates and mulberries
Keywords: Babylon; Mesopotamia; Babylonia; grown